Association Between Sulfur Dioxide and Daily Inpatient Visits With Respiratory Diseases in Ganzhou, China: A Time Series Study Based on Hospital Data - Zhou, Xingye; Gao, Yanfang; Wang, Dongming; Chen, Weihong; Zhang, Xiaokang (Frontiers in Public Health, 2022)
Background: Sulfur dioxide (SO2) has been reported to be related to the mortality of respiratory diseases, but the relationship between SO2 and the number of hospitalized patients with respiratory diseases, and potential impact of different seasons on above relationship is still unclear. Methods: Daily average concentrations of air pollutants including SO2 and meteorological data of Ganzhou, China, from 2017 to 2019 were collected. Data on daily hospitalization for respiratory diseases from the biggest hospital in this city were extracted. Generalized additive models (GAM) and the distributed lag non-linear model (DLNM) were employed to evaluate the association between ambient SO2 and daily inpatient visits for respiratory diseases. Stratified analyses by gender, age and season were performed to find the potential effects on above association. The multi-pollutant model was used to determine whether the health effects of SO2 were robust after adjusting for other air pollutants. Results: Positive exposure-response relationship between SO2 concentration and relative risk of respiratory inpatient visits. Every 10 μg/m3 increase in SO2 was related to a 3.2% (95% CI: 0.6-6.7%) exaltation in daily respiratory intpatient visits at lag3. The elderly (≥65 years) and female were more sensitive to changes of SO2. In addition, SO2 had a stronger association with respiratory inpatient visits during warm seasons (May- Oct) when compared with those during cold seasons (Nov- Apr). The relationship between SO2 and intpatient visits for respiratory diseases kept robust after adjusting for other air pollutants including PM10, NO2, O3 and CO. Conclusion: This time-series study showed that there is positive association between short-term SO2 exposure and daily respiratory intpatient visits. Furthermore, female, the elderly and warm season subgroups were more sensitive to SO2 exposure. These results are important for local administrators to formulate environmental public health policies.